Substantial Effect of Efavirenz Monotherapy on Bilirubin Levels in Healthy Volunteers - Ingrid F. Metzger, PhD; Troy C. Quigg, MD; Noam Epstein; Abdulateef O. Aregbe, MD; Nancy Thong; John T. Callaghan, MD, PhD; David A. Flockhart, MD, PhD; Anne T. Nguyen; Colleen K. Stevens; Samir K. Gupta; Zeruesenay Desta, PhD (Elsevier, 2014)
Background: Efavirenz exhibits multiple interactions with drug-metabolizing enzymes and transporters, and for this reason efavirenz-based HIV therapy is associated with altered pharmacokinetics of coadministered drugs. Probably by the same mechanism, efavirenz-based HIV therapy affects the disposition of endogenous compounds, but this effect is difficult to directly link with efavirenz because it is used in combination with other drugs. Objectives: To explore the effect of efavirenz monotherapy on biochemical laboratory values in a clinical trial of healthy volunteers. Methods: Men and women (aged 18-49 years) with body mass index ≤32 who were assessed to be healthy based on medical history, physical examination, and standard laboratory screening received a single (600 mg) and multiple doses (600 mg/d for 17 days) of efavirenz orally. This trial was designed to determine the pharmacokinetics and drug interactions of efavirenz. As part of this study, analysis of serum chemistries that were measured at study entry (screening) and 1 week after completion of the multiple dose study (exit) is reported. Results: Data from 60 subjects who fully completed and 13 subjects who partially completed the study are presented. Total bilirubin was substantially reduced at exit (by ~30%, with large intersubject variability) compared with screening values (P < 0.0001). The percent changes were in part explained by the intersubject differences in baseline total bilirubin because there was a significant correlation between baseline (screening) values and percent change at exit (r = 0.50; P < 0.0001). Hemoglobin and absolute neutropenia were also substantially decreased at exit compared with screening, but this may be due to intensive blood sampling rather than direct effect of efavirenz on these parameters. No significant correlation was found between percent change in hemoglobin versus percent change in bilirubin, indicating the effect of efavirenz on bilirubin is independent of its effects on hemoglobin. Conclusions: Efavirenz monotherapy significantly lowers plasma total bilirubin concentration in healthy volunteers independent of its effect on hemoglobin, probably through its effects on bilirubin metabolism and transport (uptake and efflux). These findings help explain reversal by efavirenz of hyperbilirubinemia induction observed by some protease inhibitor antiretroviral drugs (eg, atazanavir). Besides its well-documented role on drug interactions, efavirenz may alter the disposition of endogenous compounds relevant in physiologic homeostasis through its interaction with drug metabolizing enzymes and/or drug transporters. ClinicalTrials.gov identifier: NCT00668395.